COVID-19 in Older Individuals with Cancer: Problem and Potential Solutions. (16th March 2021) - Mohammed, Turab; Ali, Imran; Desai, Aakash
Abstract: The ongoing coronavirus disease-2019 (COVID-19) pandemic has radically affected medical practice and healthcare delivery in the United States and beyond. Its impact on vulnerable populations especially older adults battling cancer is striking. Older adults with baseline immunosenescence compounded with multimorbidity and reduced physiological reserves are at even higher risk of succumbing to infection. When it comes to older adults with cancer mortality, it often multifactorial with modifiable risk factors. A specific approach with attention to advance care planning and how cancer care is delivered coupled with a comprehensive geriatric assessment may ultimately be the key to improve overall survival.